Antioxidant Polyphenolics Extraction Techniques from Beluntas Leaves using Choline Chloride-Urea: Comparative Study with 70%-Ethanol - Hikmawanti, Ni Putu Ermi; Yumita, Agustin; Amalia, Halisa; Cahyani, Siti Rosidah; Putri, Meira Amalia; Mun'im, Abdul (MPI (Media Pharmaceutica Indonesiana), 2025)
Pluchea indica L. (Less), known as Indian camphorweed (common name) or Beluntas (Indonesia), is an antioxidant polyphenol-rich plant. In our previous studies, choline chloride-urea (CCU) at a molar ratio of 1:2 was one type of natural deep eutectic solvents (NADES) in the extraction of P. indica leaves (PIL) polyphenolics. The present study aims to evaluate the comparison of total phenolics (TPC) and flavonoids content (TFC) and antioxidant activity of CCU (1:2) extract of PIL obtained from ultrasonic-assisted extraction (UAE) and magnetic stirrer-assisted extraction (MSAE). Ethanol was used as a comparison to conventional extraction solvents. Determination of TPC and TFC was carried out using colorimetric with a microplate reader, while the antioxidant activity test was carried out using the ferric thiocyanate (FTC) method. The UAE is more effective in terms of PIL flavonoid extraction using CCU compared to MSAE, while PIL phenolic extraction with CCU is more effective with MSAE. CCU extract of PIL from extraction with MSAE at a concentration of 1.56% has an antioxidant capacity equivalent to 500 ppm ascorbic acid in inhibiting lipid peroxidation by about 70%. Thus, CCU combined with the MSAE can be recommended in further development of phenolic antioxidants extraction from PIL.